The Challenge of Inclusive Schools: No One to be Discarded - Sánchez Huete, Juan Carlos; Sánchez Gadea, Andrea (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2019)
The challenge of the inclusive school implies a specific training so that we approach a new reality that turns to be complex because of an inadequate application of regulations. Receiving a good education, which is a citizens right, is a moral duty in inclusive education. The right to education lies on three keystones: the Universal Declaration of Human Rights, the Convention of the Rights of the Child, and the Spanish Constitution. Inclusive Education guarantees the learning of all students through a set of actions aimed at eliminating, or minimizing, the barriers that limit learning.
Keywords: Inclusive Education; Equity; Equality; Functional Diversity